Overview of ICRP Committee 3: protection in medicine. (June 2016) - Vañó, E.; Miller, D.L.; Rehani, M.M.
Committee 3 of the International Commission on Radiological Protection (ICRP) develops recommendations and guidance for protection of patients, staff, and the public against radiation exposure when ionising radiation is used for medical diagnosis, therapy, or biomedical research. This paper presents a summary of the work that Committee 3 has accomplished over the past few years, and also describes its current work. The most recent reports published by the Commission that relate to radiological protection in medicine are 'Radiological protection in cone beam computed tomography' ( Publication 129 ), 'Radiation dose to patients from radiopharmaceuticals: a compendium of current information related to frequently used substances' ( Publication 128, in cooperation with Committee 2), 'Radiological protection in ion beam radiotherapy' ( Publication 127 ), 'Radiological protection in paediatric diagnostic and interventional radiology' ( Publication 121 ), 'Radiological protection in cardiology' ( Publication 120 ), and 'Radiological protection in fluoroscopically guided procedures outside the imaging department' ( Publication 117 ). A new report on diagnostic reference levels in medical imaging will provide specific advice for interventional radiology, digital imaging, computed tomography, nuclear medicine, paediatrics, and hybrid (multi-modality) imaging procedures, and is expected to be published in 2016. Committee 3 is also working on guidance for occupational radiological protection in brachytherapy, and on guidance on occupational protection issues in interventional procedures, paying particular attention to the 2011 Commission's recommendations on the occupational dose limit for the lens of the eye ( Publication 118 ). Other reports in preparation deal with justification, radiological protection in therapy with radiopharmaceuticals, radiological protection in medicine as related to individual radiosusceptibility, appropriate use of effective dose (in cooperation with other Committees), and guidance for healthcare practitioners on radiological and patient protection. Committee 3 has also suggested specific priorities for research on radiological protection in medicine to the Commission.